Genetic Polymorphisms as Risk Stratification Tool in Primary Preventive ICD Therapy. (13th April 2011) - Laszlo, Roman; Busch, Mathias C.; Schreieck, Jüergen
Abstract : More and more implantable cardioverter-defibrillators (ICDs) are implanted as primary prevention of sudden cardiac death (SCD). However, major problem in practice is to identify high-risk patients for SCD. Different methods for noninvasive risk stratification do not have a sufficient positive or negative predictive value. Since current approaches lead to implantation of ICDs in a large number of patients who will never suffer an arrhythmic event and simultaneously patients still die of SCD who currently did not seem eligible for primary preventive ICD implantation, there is a need for additional tools for risk stratification. Epidemiological studies point to a hereditary risk of SCD. Different susceptibility of each person concerning arrhythmogenic events might be explained by genetic polymorphisms. By obtaining an individual "pattern" of polymorphisms of genes encoding for proteins which are important in arrhythmogenesis in one patient, risk stratification in primary prevention of SCD might by improved.